2007
DOI: 10.1038/nature05925
|View full text |Cite
|
Sign up to set email alerts
|

Ambra1 regulates autophagy and development of the nervous system

Abstract: Autophagy is a self-degradative process involved both in basal turnover of cellular components and in response to nutrient starvation or organelle damage in a wide range of eukaryotes. During autophagy, portions of the cytoplasm are sequestered by double-membraned vesicles called autophagosomes, and are degraded after fusion with lysosomes for subsequent recycling. In vertebrates, this process acts as a pro-survival or pro-death mechanism in different physiological and pathological conditions, such as neurodeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
434
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 889 publications
(445 citation statements)
references
References 35 publications
9
434
0
2
Order By: Relevance
“…Other Atg knockout neonates, such as Atg3 (Sou et al, 2008), Atg7 (Komatsu et al, 2005), Atg9 (Saitoh et al, 2009), and Atg16L1 (Saitoh et al, 2008), also die shortly after birth. In contrast with the embryonic survival seen with these knockout mice, knockout of other autophagy genes such as beclin 1, Ambra1, and FIP200 produce other phenotypes (Fimia et al, 2007;Gan et al, 2006;Yue, Jin, Yang, Levine, & Heintz, 2003), presumably because of additional roles that these proteins play, such as regulation of endocytosis (Mizushima & Levine, 2010;Ruck et al, 2011).…”
Section: Developmental Autophagymentioning
confidence: 75%
See 1 more Smart Citation
“…Other Atg knockout neonates, such as Atg3 (Sou et al, 2008), Atg7 (Komatsu et al, 2005), Atg9 (Saitoh et al, 2009), and Atg16L1 (Saitoh et al, 2008), also die shortly after birth. In contrast with the embryonic survival seen with these knockout mice, knockout of other autophagy genes such as beclin 1, Ambra1, and FIP200 produce other phenotypes (Fimia et al, 2007;Gan et al, 2006;Yue, Jin, Yang, Levine, & Heintz, 2003), presumably because of additional roles that these proteins play, such as regulation of endocytosis (Mizushima & Levine, 2010;Ruck et al, 2011).…”
Section: Developmental Autophagymentioning
confidence: 75%
“…Ulk1 is also critical for axon outgrowth and differentiation of neurons (Tomoda, Bhatt, Kuroyanagi, Shirasawa, & Hatten, 1999). Ambra1 knockout causes early lethality in mice and also leads to pronounced defects in the central nervous system, such as neural tube closure defects and exencephaly (Fimia et al, 2007). In the heart, Atg5 deficiency results in cardiac dysfunction in adult mice (Tomoda et al, 1999).…”
Section: Developmental Autophagymentioning
confidence: 99%
“…This hypothesis was not supported by the results here obtained. Even though autophagy was recognized as a process of pivotal importance [42], its regulating genes, which have been described by numerous studies [43,44,45,46], were found to be less expressed in the embryos of the PROBIO group than in controls. We could therefore speculate that some fundamental, yet unknown, process influencing the amount of both autophagic and apoptotic messages has happened during oogenesis at class V zebrafish oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies using mice deficient for autophagy-related genes have outlined the importance of the autophagic machinery in embryonic development of the CNS [233][234][235][236]. In particular, autophagy is necessary for proper neuronal differentiation [237,238].…”
Section: Vps35 (Park17)mentioning
confidence: 99%